An Analytic Network Process Method Approach to Design Models of Lecturers Performance Evaluation - Fenny Purwani (International Journal of Artificial Intelligence Research, 2022)
One approach to greatly enhance the quality of university education level is improving the quality and career of lecturers, including services to students. Therefore, performance and work ethic are critically evaluated to obtain re-liable information. Most performance evaluations are limited to assess students in the classroom exclusively. This research employed a Multi-Criteria Decision Making (MCDM), a model designed to evaluate the lecturer’s performance and factors influencing their performance. These factors were examined from various variables, such as training and development experience, motivation, self-esteem, competency, and job satisfaction. To demonstrate the correlation and dependency among factors of lecture performance evaluation, this study employed the Analytic Network Process (ANP) method, which is part of MCDM technique. The ANP method could serve different levels of stakeholders by considering available criteria and sub-criteria. Moreover, the method could predict performance measurement of human resources by considering factors affecting lecturer’s performance. This research produced a model to evaluate lecturers’ performance effectively